Agricultural innovation and resilience in a long-lived early farming community: the 1500-year sequence at Neolithic-early Chalcolithic Çatalhöyük, central Anatolia - Bogaard, A; Filipović, D; Fairbairn, A; Green, L; Stroud, E; Fuller, D; Charles, M (Cambridge University Press, 2017)
Intensive archaeobotanical investigations at Çatalhöyük have created a unique opportunity to explore change and continuity in plant use through the c. 1500-year Neolithic-early Chalcolithic sequence of an early established farming community. The combination of crops and herd animals in the earliest (aceramic) part of the sequence reflects a distinct and diverse central Anatolian ‘package’ at the end of the 8th millennium cal BC. Here we report evidence for near continual adjustment of cropping regimes through time at Çatalhöyük, featuring recruitment of minor crops or crop contaminants to become major staples. We use panarchy theory to frame understanding of Çatalhöyük’s long-term sustainability, arguing that its resilience was a function of three key factors: its diverse initial crop spectrum, which acted as an archive for later innovations; its modular social structure, enabling small-scale experimentation and innovation in cropping at the household level; and its agglomerated social morphology, allowing successful developments to be scaled up across the wider community. This case study in long-term sustainability through flexible, changeable cropping strategies is significant not only for understanding socalled boom and bust cycles elsewhere but also for informing wider agroecological understanding of sustainable development in central Anatolia and beyond.